Peran Gender dalam Badan Legislatif Mahasiswa Pendidikan Sosiologi : Perspektif Sosiologi Organisasi - Akhtar Rio Hidayat; Farhan Pria Syawaldi; Ridho Syafiq (Jurnal Bintang Pendidikan Indonesia, 2023)
This study aims to find out about the form of gender equality within the scope of student organizations of the Sociology Education Student Legislature. This research has several problem formulations, namely 1. How do Student legislators view gender roles in the Student legislature? As well as his participation and contribution. 2. What are the obstacles to running for president of the Student Legislature? This study used a qualitative descriptive method with source triangulation as data validity. Data were obtained through observations and interviews conducted in each member of the Sociology Education Student Legislature. The results showed that from all organizations there was a majority of women as leaders of the organization, while women served as members. In this study, it can be seen that women dominate the running of the Student Legislature, in contrast to other campus government organizations that are more dominated by men.